Quadropril effectiveness and safety in women with menopausal metabolic syndrome - V. V. Skibitsky; A. V. Fendrikova; D. V. Sirotenko; T. B. Zabolotskykh; E. L. Shukhardina; S. V. Skibitskaya (Российский кардиологический журнал, 2007)
.